Biological tissue adhesive composition

By optimizing the preparation of biological tissue adhesive composition, the coordination reaction of calcium silicate and acid calcium phosphate organic inorganic materials is used to generate high adhesion and osteoinductive silicate/hydroxyapatite composite materials, the problems of insufficient adhesion and poor osteoinduction effect of existing biological tissue adhesives in bone repair are solved, and efficient fixation and regeneration and repair of bone tissue are achieved.

CN120550176AActive Publication Date: 2025-08-29HANGZHOU HUIRUISEN BIOTECHNOLOGY CO LTD

Patent Information

Application Number
CN202511062447.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-31
Publication Date
2025-08-29
Estimated Expiration
2045-07-31

AI Technical Summary

Technical Problem

The existing biological tissue adhesives have insufficient adhesion, poor bone conduction and bone induction effects in bone repair, and poor affinity with the human body, resulting in immune response and adverse effects, and are unable to achieve long-term stable fixation and bone tissue regeneration.

Method used

A powder that is cured and pulverized after curing and curing in the curing liquid is used to combine bivalent metal salts and phosphorylated amino acids to form a biological tissue adhesive through the coordination reaction of organic and inorganic materials to form a silicate/hydroxyapatite composite material with high adhesion and osteoinduction function.

Benefits of technology

It achieves high adhesion and excellent bone guidance and bone induction effects, promotes bone tissue fixation and regeneration and repair, and is suitable for bone tissue fixation, special bone defect adhesion filling and non-load-bearing part bone adhesive filling. The degradation cycle matches the autologous bone tissue reconstruction cycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120550176A_ABST
    Figure CN120550176A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biological tissue adhesives, in particular to a biological tissue adhesive composition. The biological tissue adhesive composition comprises a powder A, a powder B and a powder C, wherein the powder A is obtained by curing calcium silicate and acidic calcium phosphate in a curing liquid, curing, drying and crushing; powder B: bivalent metal salt; powder C: phosphorylated amino acid; and an aqueous solvent; the biological tissue adhesive is used for bone adhesion and bone repair. According to the biological tissue adhesive composition provided by the invention, a silicate / hydroxyapatite composite material with a bone induction function is synthesized through optimized bone cement reaction, a curing liquid is added to react with phosphorylated amino acid, and a bone adhesive material is obtained through organic and inorganic material coordination reaction; the bone repairing and regenerating capability and the bone bonding capability are good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biological tissue adhesives, in particular to a biological tissue adhesive composition. Background Art

[0002] In orthopedics, neurosurgery, and dentistry, bone defects caused by various reasons such as trauma, bone tumors, and osteomyelitis are very common, especially tooth defects. Take cavity-shaped bone defects as an example, such as extraction sockets, after bone tumor resection, pyramidal repair, and osteoporosis repair. The common feature of these parts is that they are nearly semi-closed, but there are many problems with the repair materials used clinically. Artificial bone materials have been used in bone reconstruction. The more common artificial bone materials include powders and blocks. According to the structure and performance of artificial bone materials, they can be roughly divided into inorganic materials, organic materials, and composite materials. Artificial bone materials can promote bone healing. Their working principles include: osteoconduction, where the implanted material guides bone formation by promoting the combination of host bone and the surface of the transplanted material; and osteoinduction, where the material provides a biological stimulus to induce local cells or transplanted cells to differentiate into mature osteoblasts. Currently, commonly used artificial bone materials are in the form of blocks, powders, and granules. Powders and granules have high requirements for cavity morphology and require postoperative wound protection to prevent material loss, which can lead to a decrease in bone repair effectiveness or even failure. Taking artificial cone filling in cone repair as an example, the loss of filled bone repair material can lead to poor repair results and decreased cone stability. Taking implants as an example, powdered bone repair materials require the protection of implant membranes to prevent material overflow and soft tissue intrusion into the bone formation space. In maxillary sinus surgery, the filling requirements are high, and the filling convenience of bone powder is poor. Bone repair materials with adhesive properties can better meet clinical requirements. While performing adhesive functions, they can also perform bone repair functions after implantation.

[0003] Biotissue adhesives are biomaterials used for bonding and fixation. Clinical studies have shown that bone fragment adhesives can quickly bond bone fragments, significantly shortening the healing time of fractures and bone cracks. Compared to traditional fixation methods such as plates and screws, biotissue adhesives can reduce surgical trauma and shorten postoperative recovery time. Traditional biotissue adhesives are only suitable for relatively minor fractures and bone cracks. To achieve effective fixation and adhesion, the adhesive requires a tensile strength of 2.0 MPa. Traditional biotissue adhesives have extremely low tensile strengths. They work by leveraging the anti-collapse properties of their non-aqueous system and low adhesion. They are unable to achieve long-term, stable fixation of plates, screws, implants, and bone. There are currently no ideal alternative bone adhesives on the market. Furthermore, due to their composition, traditional biotissue adhesives have poor compatibility with the human body. Excessive use can cause an immune response, leading to localized pain, swelling, and other discomfort. Furthermore, traditional biotissue adhesives have poor osteoconduction and osteoinduction properties, which can negatively impact bone tissue regeneration, and are gradually being phased out of the market.

[0004] Bone repair materials similar to biological tissue adhesives already exist, such as inorganic bone cement products. These are typically composed of calcium phosphate / phosphate salts and function through an acid-base reaction (dissolution-hydration-precipitation). Calcium phosphate cement (CPC) has attracted widespread attention in bone replacement applications due to its moldability, osteoconductivity, and biodegradability. Calcium phosphate bone cements generally consist of a solid phase, a liquid phase, and additives. The solid phase is typically a mixture of two or more powdered calcium phosphate salts (including acidic and alkaline calcium phosphates); the liquid phase can be saline, water, or a phosphate solution. After the solid and liquid phases are uniformly mixed in a prescribed ratio, a moldable paste is formed. A series of hydration reactions produce weakly crystalline hydroxyapatite crystals or calcium phosphate salts, which gradually solidify in vivo. Inorganic bone cement products have not been widely used, primarily due to insufficient strength after curing, difficulty in controlling degradation time, and a need for improved osteoinductive properties. The inorganic bone cement products currently under research and commercial sale have poor tensile and shear properties and low bonding strength due to the randomly organized entangled crystal network, and cannot be used as adhesive products for bone retention. In addition, due to the complex preparation process of inorganic bone cement products, they are rarely used in the preparation of raw materials for biomedical materials. Summary of the Invention

[0005] The present invention covers the following technical solutions: One aspect of the present invention relates to a biological tissue adhesive composition comprising: Powder A: It is obtained by solidifying and curing calcium silicate and acidic calcium phosphate in a solidifying liquid, drying and then crushing; B powder: divalent metal salt; C powder: phosphorylated amino acid; and aqueous solvents; The biological tissue adhesive is used for bone adhesion and bone repair.

[0006] According to another aspect of the present invention, it relates to a kit comprising powder A, powder B, powder C and an aqueous solvent as defined above.

[0007] According to another aspect of the present invention, there is also provided a method for preparing the biological tissue adhesive composition as described above, comprising: mixing the components, and using the resulting mixture for bone adhesion and bone repair.

[0008] The biological tissue adhesive composition provided by the present invention is synthesized through an optimized bone cement reaction to form a silicate / hydroxyapatite composite material with bone induction function. A curing liquid is added, reacting with phosphorylated amino acids, and a bone adhesive material is obtained through a coordination reaction of organic and inorganic materials. The bone adhesive material has good bone repair and regeneration ability and bone adhesion ability. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the specific embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0010] Figure 1 The figure shows the characterization of powder A provided in one embodiment of the present invention; A is the result of X-ray diffraction detection; B is a picture of powder A samples with different particle sizes; C and D are the results of electron microscopy at different magnifications.

[0011] Figure 2 This is an electron microscope image of the biological tissue adhesive after curing provided by one embodiment of the present invention. DETAILED DESCRIPTION

[0012] Reference will now be made in detail to embodiments of the present invention, one or more examples of which are described below. Each example is provided to illustrate, not to limit, the present invention. Indeed, it will be apparent to those skilled in the art that various modifications and variations may be made to the present invention without departing from the scope or spirit of the invention. For example, features illustrated or described as part of one embodiment may be used in another embodiment to produce further embodiments.

[0013] Unless otherwise indicated, all terms (including technical and scientific terms) used to disclose the present invention have the same meaning as commonly understood by one of ordinary skill in the art to which the present invention belongs. By way of further guidance, the following definitions are provided to better understand the teachings of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0014] Unless otherwise indicated, scientific and technical terms used herein have the meanings commonly understood by those skilled in the art. Furthermore, terms and laboratory procedures related to protein and nucleic acid chemistry, molecular biology, cell and tissue culture, microbiology, and immunology used herein are those widely used in the respective fields and are standard procedures. To facilitate a better understanding of the present invention, definitions and explanations of relevant terms are provided below.

[0015] The terms "and / or", "or / and", and "and / or" used in the present invention include any one of two or more related listed items, and also include any and all combinations of the related listed items, wherein the arbitrary and all combinations include any combination of two related listed items, any more related listed items, or all related listed items. It should be noted that when at least three items are connected by at least two conjunctions selected from "and / or", "or / and", and "and / or", it should be understood that in the present invention, the technical solution undoubtedly includes technical solutions connected by "logical and" and also undoubtedly includes technical solutions connected by "logical or". For example, "A and / or B" includes three parallel solutions of A, B and A+B. For example, the technical solution of "A, and / or, B, and / or, C, and / or, D" includes any one of A, B, C, and D (that is, the technical solution of all being connected by "logical OR"), and also includes any and all combinations of A, B, C, and D, that is, the combination of any two or any three of A, B, C, and D, and also includes the four-item combination of A, B, C, and D (that is, the technical solution of all being connected by "logical AND").

[0016] As used herein, the terms "comprising," "including," and "comprising" are synonymous and are inclusive or open-ended and do not exclude additional, unrecited members, elements, or method steps.

[0017] The recitation of numerical ranges herein by endpoints includes all numbers and fractions subsumed within the range, as well as the recited endpoints.

[0018] As used herein, reference to "about" a value or parameter includes (and describes) embodiments directed to the value or parameter itself. For example, a description referring to "about X" includes a description of "X."

[0019] Concentration values ​​used in this invention include fluctuations within a certain range. For example, fluctuations within a certain precision range are permitted. For example, for 2%, fluctuations within ±0.1% are permitted. For larger values ​​or values ​​that do not require overly precise control, greater fluctuations are permitted. For example, for 100g, fluctuations within ±1%, ±2%, ±5%, etc. are permitted. Regarding molecular weight, fluctuations within ±10% are permitted.

[0020] As used herein, the singular articles "a," "an," and "the" include plural referents unless otherwise indicated.

[0021] In the present invention, descriptions such as "plurality" and "multiple" refer to quantities greater than or equal to 2 unless otherwise specified.

[0022] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0023] In the present invention, "preferably", "better", "more preferably", and "suitably" are merely descriptions of preferred implementation methods or examples, and should be understood to not limit the scope of protection of the present invention. In the present invention, "optionally", "optional", and "optional" refer to being optional, that is, to being selected from either of the two parallel options of "with" or "without". If multiple "options" appear in a technical solution, unless otherwise specified and without contradiction or mutual restriction, each "optional" is independent.

[0024] All documents mentioned in the present invention are cited as references in the present invention, just as each document is cited as a reference separately. Unless they conflict with the purpose of the invention and / or technical solution of the present invention, the cited documents involved in the present invention are cited with all their contents and all their purposes. When the present invention involves cited documents, the definitions of relevant technical features, terms, nouns, phrases, etc. in the cited documents are also cited. When the present invention involves cited documents, the examples and preferred embodiments of the cited relevant technical features may also be incorporated into the present invention as references, but are limited to the ability to implement the present invention. It should be understood that when the cited content conflicts with the description in the present invention, the present invention shall prevail or be modified adaptively based on the description of the present invention.

[0025] A first aspect of the present invention relates to a biological tissue adhesive composition comprising: Powder A: It is obtained by solidifying and curing calcium silicate and acidic calcium phosphate in a solidifying liquid, drying and then crushing; B powder: divalent metal salt; C powder: phosphorylated amino acid; and aqueous solvents; The biological tissue adhesive is used for bone adhesion and bone repair.

[0026] The biological tissue adhesive composition provided by the present invention is designed based on clinical needs and has high adhesion. In some embodiments, the adhesive tensile force can reach 3MPa, with excellent bone guidance and bone induction effects. It can be used for bone tissue fixation, special bone defect adhesion filling, non-load-bearing bone adhesion filling, and promote bone tissue regeneration and repair. By generating hydroxyapatite / calcium silicate composite calcium salt as the main inorganic material raw material in the adhesive, using the composite calcium salt prepared by a specific process as the main inorganic reaction component, using phosphorylated amino acids as organic reaction components, introducing additional divalent metal salts, and generating biological tissue adhesives through coordination reactions. The biological tissue adhesive composition thus formed can be in the form of a fluid or semi-solid, such as a paste, preferably in the form of a paste. Then, the biological tissue adhesive is prepared according to the standard process for Class III sterile implants and can be directly used by qualified practitioners for human or animal subjects.

[0027] In all embodiments, a qualified practitioner, such as a physician, dentist, surgeon, nurse, or other appropriate personnel, can vary the specific components to obtain the desired adhesive properties of the biological tissue adhesive composition depending on the intended use or desired results.

[0028] The biological tissue adhesive composition can be used in a variety of applications. One object of the present invention relates to the therapeutic use of the composition according to the present invention in humans or animals, preferably its use in medical procedures, in particular during bone tissue surgery, and more preferably its use as a biological tissue adhesive in vivo. The bone tissue surgery can be dental, sinus, facial (e.g., maxillary sinus, skull) or other bony area (e.g., bone fragments, spine) surgery.

[0029] For example, biological tissue adhesive compositions can be used to adhere structures to surfaces.

[0030] The term "structure" refers to a solid object. The structure may be a bone or other bone or bone fragment, an implant, a graft, a device, or a biological tissue. Examples of biological tissue may be a tendon or a ligament, typically the anterior cruciate ligament or the posterior cruciate ligament.

[0031] The term "surface" refers to a biological surface. The biological surface may be the surface of a bone, in particular the periosteum, a thin connective membrane that surrounds the bone only on the surface not covered by cartilage, or the surface of compact bone, the peripheral and compact part of a bone, or even cancellous bone, the central part of a bone, or a tendon or ligament.

[0032] In one embodiment, the surface is prepared to receive the biological tissue adhesive composition, for example, by sharpening the surface of the bone.

[0033] In one embodiment, the adhesion of the structure to the surface by application of the biological tissue adhesive composition is permanent or intended to be permanent, or until the biological tissue adhesive composition is absorbed by or replaced by bone.

[0034] In one embodiment, a biological tissue adhesive composition is used to fill spaces, pores, or voids in the surface, either before or after placement of the structure.

[0035] In some embodiments, the biological tissue adhesive composition is used to repair bone defects caused by diseases or conditions such as cancer (eg, osteosarcoma), osteoporosis, rickets, malignant bone tumors, bone infection, or other genetic or developmental diseases.

[0036] In some embodiments, the biological tissue adhesive composition is used to strengthen bone in a subject that has been weakened by a disease or condition such as cancer (e.g., osteosarcoma), osteoporosis, rickets, a malignant bone tumor, a bone infection, or another genetic or developmental disease.

[0037] In some embodiments, the subject has suffered a trauma, such as a bone fracture, broken bone, ruptured ligament, ruptured tendon, or damaged tooth. Generally, the biological tissue adhesive composition can allow the repair of ruptured ligaments or ruptured tendons, such as during a cruciate ligament rupture, to regain mobility of the knee joint.

[0038] In some embodiments, the subject is undergoing a plastic or reconstructive surgical procedure.

[0039] The biological tissue adhesive compositions and methods can be used to aid in the treatment of subjects suffering from any disease or condition that affects the structural integrity of fibrous connective tissue.

[0040] According to another aspect, the biological tissue adhesive composition according to the present invention can be used ex vivo.

[0041] In some embodiments, the solid-liquid ratio in the A powder preparation system is 0.35 to 0.65, for example, 0.4, 0.5, or 0.6.

[0042] In some embodiments, the reaction product obtained from powder A is mainly a calcium silicate (CSH) / hydroxyapatite (HA) composite material; the pH value is 6-9.

[0043] In some embodiments, the solidification liquid is a 0.1 mol / L to 0.8 mol / L phosphate buffer solution.

[0044] Furthermore, the phosphate buffer comprises one or more of phosphoric acid, potassium dihydrogen phosphate, sodium dihydrogen phosphate, dipotassium hydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, and tripotassium phosphate.

[0045] Silicates, such as calcium silicate and bioactive glass, typically have high pH values, sometimes as high as 11-12, making them unsuitable for direct bone repair in the human body, except for root canal filling. The present invention uses calcium silicate and acidic calcium phosphate to prepare a composite calcium salt with a controllable pH value between 6 and 9 (e.g., 6.5, 7, 7.5, 8, or 8.5), making it suitable for use as an implant material and showing potential as a bone repair material and implant raw material.

[0046] In some embodiments, powder A is cured at 34°C to 40°C for 20 to 28 hours (e.g., 22 hours, 24 hours, or 26 hours), and cured at 34°C to 40°C and 95% or greater humidity for 36 to 60 hours (e.g., 40 hours, 44 hours, 48 ​​hours, 52 hours, or 56 hours). Preferably, the curing and curing temperatures are independently 36°C to 38°C.

[0047] Traditional hydroxyapatite has osteoconductivity, but weak osteoinductivity; a large number of studies have shown that silicate materials can serve as the nucleation center of hydroxyapatite, increase the expression activity of alkaline phosphatase / osteogenic differentiation level, stimulate the expression of osteoblast-related genes, stimulate specific cellular responses at the molecular level, promote the osteogenic differentiation of osteoblasts, induce hydroxyapatite-like deposition, induce and stimulate new bone formation, and have significant osteoinductivity.

[0048] The preferred A powder production reaction of the present invention is an inorganic bone cement reaction based on an acid-base reaction. It is an improved and optimized chemical precipitation reaction. Calcium silicate reacts with acidic calcium phosphate to produce a calcium silicate (CHS) / hydroxyapatite (HA) mixture. After appropriate processing, this mixture serves as the inorganic raw material A powder for biological tissue adhesives. The molecular structure and calcium-to-phosphorus ratio of HA are similar to those of the inorganic components of normal bone, resulting in good affinity with autologous bone and excellent osteoconductivity and biocompatibility. In comparison, traditional artificial chemical synthesis and animal bone processing both require high-temperature sintering to form the material. The chemical synthesis method primarily uses raw materials such as phosphoric acid, phosphates, calcium hydroxide, calcium chloride, and calcium nitrate. The reaction proceeds in a solution, and the precipitate is filtered and dried to form powder particles. This is then calcined at 750°C for 3 hours to produce a crystalline powder. This is then formed into a compact, which is then sintered at 1050°C to 1300°C to obtain hydroxyapatite. According to the definition of hydroxyapatite ceramics in GB 23101.1: hydroxyapatite, a crystalline mass of hydroxyapatite formed by the fusion of crystal grains within a powder, has a crystallinity of not less than 95%. Traditional hydroxyapatite preparation processes require high-temperature sintering, which is energy-consuming and time-consuming. Public research has shown that human bone tissue is primarily composed of low-crystalline hydroxyapatite, while high-temperature sintered hydroxyapatite is highly crystalline. Low-crystalline hydroxyapatite has significantly higher solubility and in vivo metabolic rates than high-crystalline hydroxyapatite. The problem is that, regardless of the HA preparation process, low-crystalline hydroxyapatite is typically in the form of an extremely fine powder, which cannot be directly used in clinical applications and typically requires high-temperature calcination to produce larger particles or blocks. High-crystalline HA typically degrades in vivo in excess of one year, while conventional bone defect repair takes approximately six months. The degradation rate of high-crystalline HA for bone repair is mismatched with the regeneration rate of human bone tissue.

[0049] Public research shows that calcium silicate degrades by about 50% in the body after 12 weeks. It can be inferred that the degradation period is about 24 weeks. According to the records of one embodiment of the present invention, the inorganic components in the biological tissue adhesive are the main factors that determine the degradation rate of the product. The degradation period should be about 5 to 6 months, which is highly compatible with the period of autologous bone tissue reconstruction. This process refers to the preparation technology of inorganic bone cement. The composite material of HA and calcium silicate synthesized is formed at room temperature and does not require high-temperature calcination treatment. It has both the osteoconductivity of HA and the osteoinductivity of calcium silicate. At the same time, the addition of other divalent metal salts can accelerate or adjust the degradation rate of the material and increase the biosafety and bioactivity of the product.

[0050] In some embodiments, the calcium silicate has a calcium-to-silicon ratio greater than 1.5, preferably greater than 1.8, and more preferably greater than 2.0.

[0051] In some embodiments, the calcium silicate includes one or more of tricalcium silicate, dicalcium silicate, and calcium silicate.

[0052] In some embodiments, the acidic calcium phosphate includes one or more of calcium hydrogen phosphate, calcium dihydrogen phosphate, superphosphate, and triple superphosphate.

[0053] In some embodiments, the calcium silicate and the acidic calcium phosphate are calculated based on a total weight ratio of 100 parts by weight, which is 20-80 parts by weight of calcium silicate and 20-80 parts by weight of acidic calcium phosphate; in some embodiments, the calcium silicate is 30-70 parts by weight and the acidic calcium phosphate is 30-70 parts by weight; in some embodiments, the calcium silicate is 35-65 parts by weight and the acidic calcium phosphate is 35-65 parts by weight.

[0054] In some embodiments, the B powder comprises a calcium salt.

[0055] In some embodiments, the calcium salt comprises one or more of calcium lactate, calcium gluconate, calcium citrate, calcium carbonate, calcium silicate, calcium sulfate, calcium alginate, calcium glycerophosphate, amorphous calcium phosphate, α-tricalcium phosphate, β-tricalcium phosphate, tetracalcium phosphate, calcium hydrogen phosphate, and calcium dihydrogen phosphate.

[0056] In some embodiments, the B powder further comprises one or more of a zinc compound, a magnesium compound, and a strontium compound.

[0057] In some embodiments, the C powder is porous microspheres that can quickly conduct liquid and evenly mix with the liquid phase.

[0058] In some embodiments, the phosphorylated amino acid includes one or more of phosphorylated threonine, phosphorylated tyrosine, and phosphorylated serine.

[0059] In some embodiments, the B powder is a micron-sized powder, for example, 50 μm to 150 μm, such as 80 μm, 100 μm, or 120 μm.

[0060] In some embodiments, the A powder is a micron-sized powder, for example, 50 μm to 150 μm, such as 80 μm, 100 μm, or 120 μm.

[0061] In some embodiments, powder B is preferably a bivalent metal salt with confirmed in vivo biocompatibility and a clear degradation rate, and is used to regulate the degradation rate of the biological tissue adhesive.

[0062] In some embodiments, powder B can be selected from divalent zinc salts that have synergistic osteogenesis. Zinc reduces bone resorption by inhibiting osteoclast differentiation and activity. Examples include zinc oxalate, zinc citrate, zinc glycyrrhizate, and zinc lactate. Furthermore, zinc salts with antibacterial properties, such as zinc lactate and zinc oxide, can be selected. Furthermore, zinc salts that inhibit the production of inflammatory mediators in the body and reduce inflammatory responses, such as glycyrrhizic zinc and amino acid zinc, can be selected.

[0063] In some embodiments, the biological tissue adhesive composition further comprises auxiliary components.

[0064] In some embodiments, the auxiliary component comprises at least one of a porogen, a viscoelasticity modifier, and a pH modifier.

[0065] In some embodiments, the auxiliary component includes a porogen. The porogen can regulate the porosity and degradation of the cured material. Furthermore, the porogen includes any one or more of mannitol, sorbitol, glucose, galactose, lactose, soluble starch, hydroxypropyl methylcellulose, and carboxymethyl cellulose; the particle size preferably passes through a 100-mesh sieve. The porogen content can range from 4% to 12% (based on the dry weight of the biological tissue adhesive composition); preferably, the content is 5% to 10%.

[0066] In some embodiments, the auxiliary component includes a viscoelastic modifier. This modifier can improve the brittleness and compressive strength of the cured material. Furthermore, the modifier is one or more of alginate, gelatin, xanthan gum, collagen, carrageenan, gellan gum, modified starch, pectin, gum arabic, tragacanth gum, and karaya gum; the particle size preferably passes through a 100-mesh sieve. Furthermore, the content of the viscoelastic modifier is 0.5% to 5% (of the dry weight of the biological tissue adhesive composition); preferably, the content is 1% to 4%.

[0067] The auxiliary ingredients include a pH adjuster. The pH adjuster can adjust the reaction rate of the material and the pH of the product. Furthermore, the pH adjuster includes one or more of potassium dihydrogen phosphate, sodium dihydrogen phosphate, dipotassium hydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, sodium citrate, potassium citrate, and citric acid. Furthermore, the pH adjuster is present in an amount of 1% to 5% (based on the dry weight of the biological tissue adhesive composition).

[0068] In some embodiments, the biological tissue adhesive composition comprises, by weight, 2-40 parts of powder A, 35-75 parts of powder B, and 20-45 parts of powder C. Exemplarily, the biological tissue adhesive composition comprises, by weight, 8-25 parts of powder A, 35-45 parts of powder B, and 35-45 parts of powder C.

[0069] In some embodiments, the aqueous solvent comprises water and alcohol in a volume ratio of (90-98):(2-10).

[0070] In some embodiments, the alcohol comprises one or more of PEG, glycerol, and propylene glycol.

[0071] Preferred PEG is PEG 200 to PEG 2000, such as PEG 400, PEG 500, PEG 600, and the like.

[0072] The main purposes of adding alcohol include: controlling the reaction rate; increasing the porosity of the material after the reaction; and increasing the injectability of the material.

[0073] In some embodiments, the solid-to-liquid ratio of the solid phase component in the biological tissue adhesive composition to the aqueous solvent is 0.25 to 0.45, preferably 0.30 to 0.45.

[0074] The second aspect of the present invention relates to a kit comprising powder A, powder B and powder C as defined in the first aspect.

[0075] In some embodiments, the kit further comprises auxiliary components as defined above.

[0076] As used herein, the term "kit" may refer to any article (e.g., a package or container) comprising at least one device, which includes the components of the biological tissue adhesive composition described herein. The kit may further include instructions for use, supplemental reagents, and / or components or assemblies for use in the methods or steps described herein.

[0077] Each component may be packaged separately, or one component may be separated in its container and the other two components may be mixed in the same container, or all components may be packaged together in the same container.

[0078] In one embodiment, the test kit also comprises an aqueous solvent. In this case, the aqueous solvent can be in a separate container, and other components, particularly powdered form, can be mixed in the same container or separated separately in different containers, or a component is separated in one container, and other two components are mixed in different containers. Preferably, the container used is sealed according to good packaging practice to keep the shelf life of the mixed or separated component. In certain embodiments, the shelf life of the component keeping the test kit includes keeping sterile. If additives are included in the test kit, they can be mixed with one or all components or be present in a separate container.

[0079] The kit may contain additional components for preparing or applying the adhesive composition according to the invention, such as a bowl or mixing surface, a stirring stick, a syringe, a catheter suitable for a syringe.

[0080] The third aspect of the present invention relates to a method for preparing the biological tissue adhesive composition of the first aspect, comprising mixing the components. The resulting mixture can be used for bone adhesion and bone repair.

[0081] The embodiments of the present invention will be described in detail below with reference to the examples. It should be understood that these examples are intended to illustrate the present invention only and are not intended to limit the scope of the invention. For experimental methods in the following examples where specific conditions are not specified, reference is made to the guidance provided in the present invention, and may also be made to experimental manuals or conventional conditions in the art, other experimental methods known in the art, or conditions recommended by the manufacturer.

[0082] In the following specific examples, the measured parameters of raw material components may have slight deviations within the range of weighing accuracy unless otherwise specified. For temperature and time parameters, acceptable deviations caused by instrument testing accuracy or operational accuracy are allowed.

[0083] Example 1 Preparation of biological tissue adhesive for implant retention In dental implant surgery, many patients cannot undergo immediate implantation due to insufficient bone wall height. They need to fill the tooth socket with bone powder and postpone the implantation for 6 months. This procedure increases the number of surgeries, medical costs, and medical time. Biological tissue adhesives are used for implant retention in dental implant surgery to assist in autologous bone fixation of implants, allowing immediate implantation.

[0084] Preparation of Powder A: Grind dicalcium silicate (calcium-silicon ratio 2.0) and calcium dihydrogen phosphate separately and pass through a 120-mesh sieve. Furthermore, the ratio is 50%:50%. Weigh 100g each of the pretreated calcium silicate and acidic calcium phosphate and mix in a three-dimensional mixer for 40 minutes. Prepare a phosphate buffer solution consisting of 0.5 mol / L potassium dihydrogen phosphate and 0.5 mol / L potassium dihydrogen phosphate, mix in equal volumes, and set aside. Measure 110ml of the solution at a liquid-to-solid ratio of 0.55 (ml / g). Place the mixed powder in a blender, add the curing liquid in the above proportions, and stir for 3 minutes. Once the mixture forms a paste, quickly transfer the material to a mold for pressing (at atmospheric pressure to exclude air and reduce defects and air in the material. Customized specifications can be achieved based on specific needs). Place the sample and mold in a sealed PE sample bag and cure in a 37°C incubator for 48 hours. De-mould and place in a PE sample bag without sealing, and place in a constant temperature and humidity chamber at 37°C and 100% humidity for 72 hours; the compressive strength of the cured product was measured to be 18.8 MPa. 3 The following small pieces were oven dried; further, the drying temperature was 90°C and the drying time was 48 hours; the said pieces were crushed in a grinder and passed through a 100 mesh sieve. Powder A was extracted at 0.2 g / ml at 37±1°C for 72 hours, and the pH was 7.9.

[0085] The powder A prepared in this example was tested by X-ray diffraction and showed that the composite material was composed of two components: calcium silicate (CSH) and hydroxyapatite (HA). Figure 1 Middle A); Electron microscopy shows that the synthesized material has an ordered microstructure at the nanometer / micrometer level ( Figure 1 C and D); The ordered microstructure of the composite material is conducive to the adhesion, crawling and proliferation of autologous bone cells on the surface, which also means that the material has high biological activity; at the same time, the specific surface area of ​​the material is increased, and the surface activity of the material is increased, which is conducive to the reaction and combination of the composite material with phosphorylated amino acids. After the biological tissue adhesive is cured, the calcium salt and the phosphorylated amino acids form a coordination compound, and the resulting product is denser than powder A ( Figure 2 ), and some porogens are added to give the material some macroporous structures, which are more conducive to gradient degradation and guiding bone cell growth.

[0086] Powder B treatment: Calcium citrate is crushed with a grinder, passed through a 100-mesh stainless steel sieve, and weighed according to the formula ratio for later use; Other auxiliary ingredients include porogen, viscoelastic regulator and pH regulator, which are crushed by a grinder, passed through a 100-mesh stainless steel sieve, and weighed according to the formula ratio for later use.

[0087] Weigh 20g of powder A; 35g of powder B (calcium citrate); 35g of powder C (phosphotyrosine); 5g of the auxiliary ingredients, including mannitol (porogen), 2g of medical gelatin (viscoelastic modifier), 1g of trisodium phosphate, and 2g of disodium hydrogen phosphate (pH modifiers). Combine 100g of these ingredients in a mixing bowl. Mix powder A, powder B, and other auxiliary ingredients uniformly for 30 minutes. Add powder C and mix for 30 minutes. Dispense into 2g packages and sterilize with Cobalt-60.

[0088] To prepare the aqueous solvent, weigh 95g of purified water and 5g of PEG400, mix well, and dispense into 1ml portions. The dry powder is mixed with the liquid phase at a liquid-to-solid ratio of 0.3. 2 g of dry powder and 0.6 ml of aqueous solvent are taken and mixed and stirred to form a bone adhesive material with a certain viscosity. This material can be solidified in water. The material was tested and the bonding tensile force was 3.2 MPa. The strength of the material after solidification was 38 MPa and the pH of the material was 7.1.

[0089] Example 2 Preparation of maxillary sinus filling material In implant surgery, maxillary sinus lift is a highly demanding procedure for the surgeon. This procedure allows the implant to take root more deeply in the jawbone, integrating with more bone tissue, thereby improving its stability and addressing issues of insufficient bone mass or insufficient bone wall thickness. The separation of the maxillary sinus mucosa from the bone tissue places high demands on surgical materials. Pastes are superior to granular materials in terms of performance and ease of delivery, while simultaneously securing the implant and greatly facilitating clinical procedures. Furthermore, by promoting the regenerative integration of the implant with the jawbone, long-term results are achieved. To facilitate infusion, the non-aqueous liquid in this material's curing solution is prepared at the maximum volume.

[0090] Preparation of Powder A: Calcium silicate (calcium-silicon ratio 2.5) and calcium dihydrogen phosphate were ground separately and passed through a 120-mesh sieve. Weigh 55g of the sieved calcium silicate and 45g of the calcium dihydrogen phosphate, respectively, and mix in a three-dimensional mixer for 50 minutes. A phosphate buffer solution consisting of 0.5 mol / L sodium dihydrogen phosphate and 0.4 mol / L trisodium phosphate was prepared, mixed in equal volumes, and set aside. Measure 50ml of the mixture at a liquid-to-solid ratio of 0.50 (ml / g). Place the mixed powder in a blender and add the curing liquid in the above proportions. Stir for 3 minutes. Once the mixture forms a paste, quickly transfer the material to a mold for pressing (at atmospheric pressure to exclude air and reduce defects and air in the material. Customized specifications can be achieved based on specific needs). The sample and mold were sealed in a PE sample bag and cured in a 37°C incubator for 36 hours. De-mould and place in a PE sample bag without sealing, and place in a constant temperature and humidity chamber at 37°C and 100% humidity for 48 hours; the compressive strength of the cured product was measured to be 21.3 MPa. 3 The following small pieces were oven-dried at 60°C for 60 hours. The dried pieces were crushed in a grinder and passed through a 100-mesh sieve. Powder A was extracted at 0.2 g / ml at 37±1°C for 72 hours, with a pH of 8.5.

[0091] Powder B treatment: Calcium carbonate is crushed with a grinder, passed through a 100-mesh stainless steel sieve, and weighed according to the formula ratio for later use; The other auxiliary ingredients are crushed separately using a grinder, passed through a 100-mesh stainless steel sieve, and weighed according to the formula ratio for later use.

[0092] Weigh 10g of powder A; 40g of powder B (calcium carbonate); 40g of powder C (phosphorylated serine); and 6g of the auxiliary ingredients, including soluble starch as a pore-forming agent, 1g of carrageenan as a viscoelastic modifier, and 3g of trisodium phosphate as a pH adjuster. Combine these ingredients for a total of 100g. Mix powders A, B, and other auxiliary ingredients in a mixing vessel for 40 minutes. Add powder C and mix for 30 minutes. Dispense into 1g packages and sterilize with Cobalt-60.

[0093] To prepare the aqueous solvent, weigh 90 g purified water and 10 g PEG400, mix well, and dispense into 1 ml portions. The dry powder was mixed with the liquid phase at a liquid-to-solid ratio of 0.35 to form a bone adhesive material with a certain viscosity. This material can solidify in water and can be delivered with a syringe. The material was tested for bonding tensile strength, and the test result was 3.1 MPa. After solidification, the material strength was 37 MPa and the pH was 7.4.

[0094] Example 3 Preparation of skull tissue adhesive During skull surgeries, many resected skull bones need to be reattached and re-implanted. This is often done with screws and plates, often made of materials like titanium alloy and PEEK. These non-degradable materials remain in the body for long periods of time, potentially causing problems. Especially for adolescents undergoing development, non-degradable screws and plates may interfere with normal skull growth, necessitating subsequent removal. Skull locks are generally divided into two types: non-absorbable and absorbable. Non-absorbable ones are typically made of titanium alloy and are lifelong. Absorbable ones are typically made of polylactic acid or polypropionic acid and are typically decomposed and absorbed within 1-2 years of implantation. However, polylactic acid produces acid during degradation, which is detrimental to bone healing. Biological tissue adhesives can play a role in skull reduction, similar to the bonding effect of cement in building walls. The adhesive initially provides bone-to-bone bonding and then degrades during bone regeneration, promoting skull regeneration.

[0095] Preparation of Powder A: Grind tricalcium silicate (calcium-silicon ratio 3.0) and triple superphosphate separately and pass through a 120-mesh sieve. Weigh 52g of the sieved calcium silicate and 48g of calcium dihydrogen phosphate, respectively, and mix in a three-dimensional mixer for 30 minutes. Prepare a phosphate buffer solution consisting of 0.4 mol / L sodium dihydrogen phosphate and 0.5 mol / L trisodium phosphate, mixing in equal volumes. Measure 45ml at a liquid-to-solid ratio of 0.45 (ml / g). Place the mixed powder in a blender and add the curing liquid in the above proportions. Stir for 3 minutes. Once the mixture forms a paste, quickly transfer the material to a mold for pressing (pressing at atmospheric pressure to exclude air and reduce defects and air in the material. Customized specifications can be achieved based on specific needs). Place the sample and mold in a sealed PE bag and cure in a 37°C incubator for 24 hours. De-mould and place in a PE sample bag without sealing, and place in a constant temperature and humidity chamber at 37°C and 100% humidity for 48 hours; the compressive strength of the cured product was measured to be 23.3 MPa. 3The following small pieces were dried in an oven at 50°C for 40 hours. The dried pieces were crushed in a grinder and passed through a 100-mesh sieve. Powder A was extracted at 0.2 g / ml at 37±1°C for 72 hours, with a pH of 7.3. Treatment of powder B: Glycerophosphate calcium is crushed with a grinder, passed through a 100-mesh stainless steel sieve, and weighed according to the formula ratio for later use; other auxiliary ingredients are crushed separately with a grinder, crushed through a 100-mesh stainless steel sieve, and weighed according to the formula ratio for later use.

[0096] Weigh 15g of powder A; 35g of calcium glycerophosphate powder B; 40g of phosphorylated serine powder C; 5g of glucose as a pore former; 2g of hydroxyethyl starch as a viscoelastic modifier; and 3g of potassium dihydrogen phosphate as a pH adjuster. The total is 100g. Mix powders A, B, and other auxiliary ingredients in a mixing bowl for 50 minutes. Add powder C and mix for 35 minutes. Dispense into 3g packages and sterilize with ethylene oxide.

[0097] Prepare aqueous solvent by weighing 97g purified water and 3g glycerol, mix well, and dispense into 2ml portions. The dry powder was mixed with the liquid phase at a liquid-to-solid ratio of 0.32 to form a bone adhesive material with a certain viscosity, which can be solidified in water. The material was tested for bonding tensile strength, and the test result was 2.9 MPa. The strength of the material after solidification was 42 MPa and the pH was 7.3.

[0098] Example 4 Preparation of Bone-Crushing Biological Tissue Adhesive Compared with other materials, autologous bone transplantation has a better regenerative effect. In general orthopedic surgery, comminuted fractures / surgical bone fragments backfilling is a challenge for doctors. Using ordinary adhesive materials to adhere to the bone fragments cannot ensure that the bone fragments occupy the position for a long time. Using water-resistant adhesives can reduce surgical operation requirements and ensure surgical results. Using osteoinductive adhesive materials can adhere to the bone fragments, facilitate autologous bone restoration, and better promote bone tissue regeneration and repair.

[0099] Preparation of Powder A: Grind tricalcium silicate / dicalcium silicate, and calcium monohydrogen phosphate separately and pass through a 120-mesh sieve. Weigh the pretreated materials according to the formula ratio and mix in a three-dimensional mixer for 40 minutes. The formula ratio is 36% tricalcium silicate, 18% calcium silicate, and 46% calcium monohydrogen phosphate. Weigh 36g of tricalcium silicate, 18g of dicalcium silicate, and 46g of calcium monohydrogen phosphate. Prepare a phosphate buffer solution consisting of 0.5 mol / L phosphoric acid and 0.5 mol / L tripotassium phosphate in equal volumes and set aside. Measure 52ml for a liquid-to-solid ratio of 0.52. Place the mixed powder in a blender and add the curing liquid according to the above ratio. Stir for 3 minutes. Once the mixture forms a paste, quickly transfer the material to a mold for pressing (at atmospheric pressure to exclude air and reduce defects and air in the material. Customized specifications can be pressed according to specific needs). Place the sample and mold in a sealed PE sample bag and cure in a 37°C incubator for 24 hours. De-mould and place in a PE sample bag without sealing, and place in a constant temperature and humidity chamber at 37°C and 100% humidity for 60 hours; the compressive strength was measured to be 20.4 MPa. 3 The following small pieces were placed in an oven and dried; further, the drying temperature was 90°C and the drying time was 50 hours; the blocks were crushed in a grinder and passed through a 100-mesh sieve. Powder A was extracted at 0.2 g / ml, 37±1°C, for 72 hours, and the pH was 8.5;

[0100] Powder B treatment: Calcium alginate is crushed with a grinder, passed through a 100-mesh stainless steel sieve, and weighed according to the formula ratio for later use; The other auxiliary ingredients are crushed separately using a grinder, passed through a 100-mesh stainless steel sieve, and weighed according to the formula ratio for later use.

[0101] Weigh 5g of powder A; 42g of calcium alginate (B); 43g of phosphorylated threonine (C); 6g of mannitol (porogen); 2g of potassium alginate (viscoelastic modifier); and 2g of trisodium phosphate (pH adjuster). The total is 100g. Mix powders A, B, and other auxiliary ingredients in a mixing bowl for 30 minutes. Add powder C and mix for 30 minutes. Dispense into 3g packages and sterilize with ethylene oxide.

[0102] Prepare aqueous solvent by weighing 96g purified water and 4g glycerol, mixing well and dispensing in 2ml portions. The dry powder was mixed with the liquid phase at a liquid-to-solid ratio of 0.30 to form a bone adhesive material with a certain viscosity. This material can be cured in water. The material was tested for tensile strength and the result was 3.3 MPa. The strength of the cured material was 46 MPa. The pH was 7.0.

[0103] Example 5 Preparation of Viscous Bone Material for Intervertebral Fusion Autologous iliac bone fragments or artificial bone powder are commonly used as bone fillers in intervertebral fusion surgery. However, these materials are difficult to implant and are easily lost in the body, reducing the repair effect. Using bio-tissue adhesives through injection allows the material to remain stable in the body for a long time, reducing the use of autologous bone and avoiding secondary surgeries while maintaining the therapeutic effect of intervertebral fusion. To facilitate injection, the proportion of non-aqueous liquid in the curing fluid is increased, improving the injectability of the mixed material.

[0104] Preparation of Powder A: Calcium silicate (calcium-silicon ratio 2.5) and triple superphosphate are separately ground and passed through a 120-mesh sieve. The pretreated materials are weighed according to the formula ratio and mixed in a three-dimensional mixer for 40 minutes. Furthermore, the formula ratio is 60% calcium silicate and 40% triple superphosphate. These powders are weighed according to the formula ratio and passed through a 120-mesh sieve. The pretreated materials are weighed according to the formula ratio and mixed in a three-dimensional mixer for 40 minutes. Weigh 60g of calcium silicate and 40g of triple superphosphate according to the formula. This mixture is placed in a blender with equal volumes of 0.5mol / L dipotassium hydrogen phosphate and 0.4mol / L potassium dihydrogen phosphate in a phosphate buffer solution. At a liquid-to-solid ratio of 0.45, 45ml of curing solution is added according to the above ratio and stirred for 3 minutes. Once the mixture becomes a paste, the material is quickly transferred to a mold for pressing (at atmospheric pressure to exclude air and reduce defects and air in the material. Customized specifications can be achieved based on specific needs). The sample and mold were placed in a PE sample bag, sealed, and placed in a constant temperature incubator at 37°C for 48 hours to cure. After demoulding, the sample was placed in a PE sample bag without sealing and placed in a constant temperature and humidity chamber at 37°C and 100% humidity for 48 hours. The compressive strength of the cured product was measured to be 20.6 MPa. Initial crushing was performed, and the fragments were broken into 1 cm pieces. 3 The following small pieces were placed in an oven and dried; further, the drying temperature was 75°C and the drying time was 36 hours; the blocks were crushed in a grinder and passed through a 100-mesh sieve. Powder A was extracted at 0.2 g / ml, 37±1°C, for 48 hours, and the pH was 7.0; Powder B treatment: Calcium lactate is crushed with a grinder, passed through a 100-mesh stainless steel sieve, and weighed according to the formula ratio for later use; The other auxiliary ingredients are crushed separately using a grinder, passed through a 100-mesh stainless steel sieve, and weighed according to the formula ratio for later use.

[0105] Weigh 8g of powder A; 45g of calcium lactate powder B; 37g of phosphorylated tyrosine powder C; 5g of galactose (porogen); 3g of hydroxypropyl methylcellulose (viscoelastic modifier); and 2g of dipotassium hydrogen phosphate (pH adjuster). The total is 100g. Mix powders A, B, and other auxiliary ingredients in a mixing bowl for 40 minutes. Add powder C and mix for 30 minutes. Dispense into 3g packages and sterilize with Cobalt-60.

[0106] Prepare aqueous solvent by weighing 91g purified water and 9g glycerol, mix well, and dispense into 2ml portions. The dry powder was mixed with a curing liquid at a liquid-to-solid ratio of 0.38 to form a bone adhesive material with a certain viscosity. This material can be cured in water and transferred to a syringe for injection. The material was tested for bond tensile strength, which was 2.9 MPa. The strength of the cured material was 40 MPa and the pH was 7.0.

[0107] Experimental Example 1 Study on the liquid-to-solid ratio of biological tissue adhesive: To determine the appropriate liquid-to-solid ratio, we conducted research experiments based on Example 2 and analyzed and screened the formulations. The liquid-to-solid ratio was selected based on operability and viscosity (tensile strength) greater than 2.0 MPa. The details are as follows:

[0108] Experimental Example 2 Other conditions were fixed and the inorganic / organic content in the material was adjusted. Powder A was prepared according to the process conditions of Example 5, without powder B, and powder C was phosphorylated tyrosine. The auxiliary ingredients were fixed according to the conditions of Example 5, totaling 10 g. Three samples were obtained and tested for adhesion (tensile strength). The results showed that the inorganic / organic content significantly affected the curing time of the material and the adhesion performance of the product. In this basic formula, within the experimental range, the adhesion strength decreased with increasing phosphorylated tyrosine content.

[0109]

[0110] Experimental Example 3 The study compared the effects of A powder composite calcium salt and high crystallinity HA on degradation; in vitro degradation tests can simulate the in vivo degradation process under controlled conditions, especially the research and speculation on degradation rate, providing preliminary data support for in vivo tests and optimizing material formulation and manufacturing process.

[0111] In vitro simulated degradation experiments: Powder A composite calcium salt was prepared according to Examples 1-5. Several cylinders with a diameter of 0.6 cm and a height of 1.0 cm were prepared and numbered. Each cylinder was dried to a constant weight and weighed (m1). The cylinders were immersed in Tris-HCl buffer and shaken at 37°C. After 7, 14, 21, 28, and 56 days, the cylinders were removed, dried to a constant weight, and weighed (m2). The weight loss on drying was (m1 - m2) / m1. The phosphorus content of powder A was determined using the quinoline phosphomolybdate gravimetric method, and the hydroxyapatite content was converted. The hydroxyapatite content of Examples 1-5 is shown in the following table. Because both PBS and SBF buffers contain phosphate ions, which may form hydroxyapatite under the action of silicates, affecting the test results, Tris-HCl buffer was used in this experiment.

[0112] Control Sample 1 was made from hydroxyapatite powder, while Control Sample 2 was made from calcium silicate / hydroxyapatite powder (mass ratio 4:6). Bioceramic materials (Control Samples 1 and 2) were prepared using the following process: A 5% polyvinyl alcohol solution was used as a binder, and the powder and polyvinyl alcohol solution were mixed in a mass ratio of 92:8. The mixture was stirred evenly, filled into a 0.6 cm diameter and 1.0 cm height mold, and pressed into shape. The mold was then sintered in a 1150°C furnace for 6 hours and cooled to room temperature to produce hydroxyapatite bioceramic (Control Sample 1) and calcium hydroxysilicate / hydroxyapatite composite bioceramic (Control Sample 2), respectively. In vitro weight loss testing was performed using the same method as in Examples 1-5 for preparing the composite calcium salt of powder A.

[0113] The results showed that the composite calcium salts of powder A prepared in Examples 1-5 lost weight significantly faster than the control samples. Control Sample 1, composed of pure hydroxyapatite (HA), exhibited the lowest weight loss, consistent with published research. The greater weight loss in the first week was likely due to debris shedding. Control Sample 2, a high-temperature calcined calcium silicate / hydroxyapatite composite bioceramic, exhibited a significantly lower weight loss rate than the samples in Examples 1-5, despite a lower HA content than in the experimental examples. This suggests that high-temperature calcination of HA significantly impacts the degradation properties of the composite. The composite calcium salts of powder A prepared in Examples 1-5 degraded rapidly. In addition to the presence of silicate in the composite, which accelerated degradation, the degradation rate of low-crystallinity hydroxyapatite was also significantly faster than that of calcined high-crystallinity hydroxyapatite. These results suggest that the inorganic components of the biotissue adhesive are the primary factor determining the degradation rate of the product. The composite calcium salts of powder A prepared in Examples 1-5 should have an in vitro degradation period of approximately six months, which closely matches the period of autologous bone tissue reconstruction. It is reasonable to speculate that the introduction of powders B and C could further reduce the degradation rate of the product.

[0114]

[0115] Experimental Example 4 According to GB / T 16886.12-2023, Biological Evaluation of Medical Devices, the cytotoxicity of the biological tissue adhesive products of Examples 1-5 was evaluated using an indirect contact method (MTT assay). The cells were extracted with complete culture medium at a ratio of 0.2 g / ml at (37±1)°C for 72 h. Different concentrations of the extracts of the products of Examples 1-5 (50% and 100%) were added to the culture medium of mouse fibroblasts (L929) cultured in vitro. MTT assay was used to visualize the cells 2, 4, and 7 days after inoculation. The absorbance was measured at 450 nm on a microplate reader, and the relative proliferation rate was calculated and evaluated. Results: Over time, different concentrations of the extracts of the products of Examples 1-5 promoted L929 cell proliferation. There were no significant differences in L929 cell numbers or morphological changes in each experimental group compared with the negative control group. The cytotoxicity of the products of Examples 1-5 was scored as 0-1. Conclusion: The products of Examples 1-5 exhibited no significant cytotoxicity and demonstrated good cytocompatibility.

[0116]

[0117] The above-described embodiments merely represent several implementation methods of the present invention, and their descriptions are relatively specific and detailed, but they should not be construed as limiting the scope of the patent. It should be noted that a person skilled in the art may make several modifications and improvements without departing from the concept of the present invention, and these modifications and improvements fall within the scope of protection of the present invention. Therefore, the scope of protection of the patent for this invention shall be based on the appended claims, and the description and drawings may be used to interpret the content of the claims.

Claims

1. A biological tissue adhesive composition, characterized in that Include: Powder A: It is obtained by solidifying and curing calcium silicate and acidic calcium phosphate in a solidifying liquid, drying and then crushing; B powder: divalent metal salt; C powder: phosphorylated amino acid; and aqueous solvents; The biological tissue adhesive is used for bone adhesion and bone repair.

2. The biological tissue adhesive composition according to claim 1, characterized in that The solid-liquid ratio in the A powder preparation system is 0.35-0.65; The solidifying liquid is 0.1mol / L to 0.8mol / L phosphate buffer; The curing conditions of powder A are 34°C to 40°C for 20h to 28h, and the curing conditions are 34°C to 40°C and a humidity of more than 95% for 36h to 60h.

3. The biological tissue adhesive composition according to claim 1 or 2, characterized in that The calcium silicate and the acidic calcium phosphate are calculated based on 100 parts by weight of the total amount, and the calcium silicate comprises 20 to 80 parts and the acidic calcium phosphate comprises 20 to 80 parts.

4. The biological tissue adhesive composition according to claim 1, characterized in that The divalent metal salt comprises a calcium salt.

5. The biological tissue adhesive composition according to claim 1, characterized in that The C powder is porous microspheres.

6. The biological tissue adhesive composition according to any one of claims 1, 2, 4, and 5, characterized in that: The invention further comprises auxiliary components, wherein the auxiliary components comprise at least one of a porogen, a viscoelasticity regulator and a pH regulator.

7. The biological tissue adhesive composition according to any one of claims 1, 2, 4, and 5, characterized in that: In parts by weight, it comprises 2 to 40 parts of A powder, 35 to 75 parts of B powder, and 20 to 45 parts of C powder.

8. The biological tissue adhesive composition according to claim 7, characterized in that The aqueous solvent comprises water and alcohol in a volume ratio of (90-98):(2-10); The alcohol comprises one or more of PEG, glycerol, and propylene glycol; The solid-to-liquid ratio of the solid phase component in the composition to the aqueous solvent is 0.25 to 0.

45.

9. A kit, characterized in that The invention comprises the powder A, powder B, powder C and an aqueous solvent as defined in any one of claims 1 to 8.

10. The method for preparing the biological tissue adhesive composition according to any one of claims 1 to 8, characterized in that: include: The components are mixed and the resulting mixture is used for bone bonding and bone repair.

Citation Information

Patent Citations

  • Hydrogen phosphate / tricalcium silicate composite self-curing material with biological activity, preparation and uses thereof

    CN101428153A

  • Pre-mixed calcium silicate / magnesium phosphate double-phase composite self-solidification root canal filling material and preparation method and application thereof

    CN107411976A

  • Endodontic filling material

    US20080206716A1

  • Organophosphorous & multivalent metal compound compositions & methods

    US20120288446A1

  • Bioadhesive composition

    WO2024133597A1

Cited By

  • Multi-cooperative regulation composite bone adhesion system and preparation method and application thereof

    CN122140984A